Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

I can't find where I went wrong!! Can anybody please find it for me? We already have: tan(Π-x)=-tan(x); --(1) and tan(-x)=-tan(x); --(2) So we start: Let x = tan -1 (-y), Then -y = tan(x); => y = -tan(x); => y = tan(Π-X) and y = tan(-x) using (1) and (2) => Π-x=tan -1 (y) and -x= tan -1 (y) => -x = tan -1 (y)-Π and -x = tan -1 (y) => x = Π - tan -1 (y) and x = -tan -1 (y) => Π - tan -1 (y) = - tan -1 (y) => Π = 0 How can it be possible? Where I went wrong?? Please help me!

I can't find where I went wrong!! Can anybody please find it for me?


We already have:


tan(Π-x)=-tan(x); --(1)


and


tan(-x)=-tan(x); --(2)


So we start:


Let x = tan-1(-y),


Then -y = tan(x);


=> y = -tan(x);


=> y = tan(Π-X) and y = tan(-x) using (1) and (2)


=> Π-x=tan-1(y) and -x= tan-1(y)


=> -x = tan-1(y)-Π and -x = tan-1(y)


=> x = Π - tan-1(y) and x = -tan-1(y)


=> Π - tan-1(y) = - tan-1(y)


=> Π = 0


How can it be possible? Where I went wrong??


Please help me!

Grade:12

2 Answers

SAGAR SINGH - IIT DELHI
879 Points
10 years ago

Dear student,

Please go thru Inverse trignometric  functions, There are some coditions when inverse of a function is applied.....

Davis Devasia
31 Points
10 years ago

Can you please note it here? I couldn't find where I am wrong!

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free